OBSERVATIONS ON THE REPRODUCTIVE BEHAVIOR OF INDIAN PEAFOWL (PAVO CRISTATUS LINN.) UNDER CAPTIVITY - J. Naseer; K. M. Anjum; W. A. Khan; M. Imran; A. Yaqub; M. A. Munir; A. Nazeer (Journal of Animal and Plant Sciences, 2018)
Indian peafowl, Pavo cristatus (P. cristatus) is a beautiful bird but its population is declining in the wild and currently it is declared as a threatened species according to International Union for Conservation of Nature (IUCN). Therefore, captive breeding of this species is common for its conservation.The present study was designed to elucidate various parameters of sexual behavior of this bird, such as breeding season, clutch size, hatching time, age at maturity of both male and female and breeding interval under captive conditions in Punjab, Pakistan. It was observed that the mean clutch size of P. cristatus at one captive site, government zoological gardens, was 8.6±0.55eggs and at the other captive site (private sectors) were 7.24±0.6 eggs. Female birds spent more time in feeding and less time in standing compared to their respective males. Similarly, females spent significantly more time in walking and running but less time in sitting, preening and calling compared to their respective males. Indian peafowls breed from May to August at the two field captive sites.Time for hatching of eggs of P. cristatus was observed to be 27.92±0.17days and 27.96±0.12days at the government and private sites, respectively. At these sites, the bird breeds only once in a year. Age at reproductive maturity of female Indian peafowl was 2.41±0.13 years and 2.26±0.12 years and of male was 2.65±0.65 and 2.71±0.63 years, respectively at both government and private captivity sectors.The results of the present study should be helpful especially to farmers for information concerning the breeding season and behavioral activities of the bird under captivity. Furthermore, breeders will be able to timely implement proper management practices before the onset of the breeding season of this bird in order to obtainmore fruitful results in terms of their business.
Keywords: Breeding Pattern; Reproductive Behavior; Captive Breeding; Indian peafowl; Pakistan